Pengurangan Kantong Plastik Sekali Pakai di Pasar di Indonesia: Penerapan Extended Theory of Planned Behavior - Tambun, Elita Tri Nacia; Nastiti, Anindrya (Jurnal Sosioteknologi, 2025)
Despite significantly adverse environmental and health effects, single-use plastic bags have been a popular choice in many retail stores and traditional markets for purchasing. Public awareness and participation primarily support the policy to reduce the use of single-use plastic bags. This study seeks to identify factors influencing consumers' intention to reduce their use of single-use plastic bags. This study surveyed 140 consumers in two traditional markets in the heart of Bandung, Indonesia, using the extended Theory of Planned Behavior (TPB). The majority of respondents have a strong intention to reduce the use of single-use plastic bags. Significant predictors of this intention are attitude toward behavior and perceived behavioral control, whereas subjective norms, environmental awareness, laws, and regulations do not significantly affect the intention to reduce single-use plastic bags among the consumers. We propose both demand-side and supply-side interventions to achieve greater reductions of singleuse plastic bags in the traditional markets.